Upaya peningkatan pemahaman makna simbol-simbol pancasila melalui model mind mapping pada siswa kelas III sekolah dasar - Abid Nasrullah; Hasan Mahfud; Fadhil Purnama Adi (Didaktika Dwija Indria, 2020)
The purpose of this study was to increased  the understanding of the meaning of the pancasila symbol with a Mind Mapping model in SD Negeri Tunggulsari 1 school year 2019/2020. The researching is a Classroom Action Research at elementary school  concocted in two cycles. every cycle consists of four stages, there are: planning, action, observation, and reflection. The technique to collect data, there are documentation, interviews, observation, and tests. The result of data collection were used as the source of triangulation and triangulation methods.The data analysis was performed of using interactive analysis technique. The first cycle resulted in a percentage of 54,54% and the study continued with the second cycle with the percentage of 90,90%. the outcome of research shows that the use Mind Mapping model can increased  the understanding of the meaning of pancasila symbols at SD Negeri Tunggulsari 1 school years 2019/2020.